2001
DOI: 10.1590/s0037-86822001000100014
|View full text |Cite
|
Sign up to set email alerts
|

Comparação de quatro métodos laboratoriais para diagnóstico da Giardia lamblia em fezes de crianças residentes em Belém, Pará

Abstract: We report the evaluation of four techniques for Giardia lamblia diagnosis in children's stool. The Iron haematoxilin staining and direct examination with lugol showed lower positivity, while the method of Faust et al. Continues to be a good option for G. lamblia diagnosis and Immunoenzymatic assay increases the detection of this parasite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
(7 reference statements)
0
7
0
4
Order By: Relevance
“…A utilização de teste imunoenzimático para pesquisa de coproantígenos é indicada em estudos epidemiológicos para o diagnóstico coletivo ou de populações e em casos isolados com clínica sugestiva e as metodologias microscópicas são inconclusivas (Chapman et al, 1990;Machado et al, 2001;Póvoa et al, 2000). O Cryptosporidium é a causa mais comum de diarréia entre as crianças admitidas, mesmo em associação com outros enteropatógenos.…”
unclassified
“…A utilização de teste imunoenzimático para pesquisa de coproantígenos é indicada em estudos epidemiológicos para o diagnóstico coletivo ou de populações e em casos isolados com clínica sugestiva e as metodologias microscópicas são inconclusivas (Chapman et al, 1990;Machado et al, 2001;Póvoa et al, 2000). O Cryptosporidium é a causa mais comum de diarréia entre as crianças admitidas, mesmo em associação com outros enteropatógenos.…”
unclassified
“…Another important aspect related to the sensitivity of these techniques is their ability to detect small quantities of antigens, enabling diagnosis even when the parasite load in the sample is low. This fact was previously confirmed by Machado et al (MACHADO et al, 2001), who used ELISA to identify the presence of Giardia lamblia in children's stools, while traditional coprological techniques failed to detect any presence.…”
Section: Resultsmentioning
confidence: 69%
“…High sensitivity of cyst and oocyst recovery has been demonstrated by several authors. Machado et al (2001) reported that the technique of Faust showed higher positivity of G. duodenalis in the feces of children than did iron hematoxylin, direct examination using Lugol's solution or enzyme immunoassay. Likewise, Huber et al (2003) showed higher frequency of Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%